KNOWLEDGE, ATTITUDE, AND PRACTICES OF MOTHERS TOWARDS CHILD IMMUNISATION AT GOMBE DISTRICT HOSPITAL, BUTAMBALA DISTRICT. ACROSS-SECTIONAL STUDY. - Namutebi, Resty; Anywar , Lydia (Student's Journal of Health Research Africa, 2024)
Introduction Immunization is the process whereby a person is made immune or resistant to an infectious disease, typically by administering a vaccine. These vaccines help to stimulate the body’s immune system to protect the person against subsequent infection or disease. Methodology This was a cross-sectional study that employed a random sampling method and each participant was assessed using a pre-designed questionnaire. Data was analyzed by use of paper, pens, and tallying and presented in tables and pie-charts for easy interpretation Results majority 63.2% had heard about immunization before, 50% knew that the importance of immunization was to strengthen their children’s ability to fight against childhood immunizable diseases, attitude of mothers towards immunization majority 90% agreed that immunization was of importance towards a child’s health, most of the mothers (79%) say they would encourage other mothers to bring their children for immunization majority of the mothers (64.2%) believe it’s safe to vaccinate their children. Regarding practices of mothers towards immunization; the majority (77.9%) fully immunize their children and the minority (22.1%) did not fully immunize their children because of the fear of the post-vaccination side effects. Conclusion majority of the mothers know child immunization, its importance towards their children’s health, and when a child needs to be vaccinated, the vids and the recommended sites for different vaccines, mothers generally had good attitude towards immunization of children since all had ever brought their children for immunization and mothers had good practices for immunization of their children which was portrayed by most of the children being fully immunized. Recommendation Government should come up with programs creating awareness concerning the importance of child immunization and delivery of immunization services at all health facilities among various communities as this is associated with a higher likelihood of child immunization.